2020
DOI: 10.1021/acs.est.0c01084
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Superhydrophobic Metal-Based Carbon Nanotube Membrane for Electrochemically Enhanced Water Treatment

Abstract: Treatment of highly saline wastewaters via conventional technology is a key challenging issue, which calls for efficient desalination membranes featuring high flux and rejection, low fouling, and excellent stability. Herein, we report a high-strength and flexible electro-conductive stainless steel-carbon nanotube (SS-CNT) membrane, exhibiting significantly enhanced anticorrosion and antifouling ability via a microelectrical field-coupling strategy during membrane distillation. The membrane substrates exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Omi et al [55] fabricated CNT-based ERMs via a vacuum-assisted layer-by-layer method. Also, electrophoretic deposition [56] and chemical vapor deposition [17] have been used to obtain hollow fiber type rGO-CNT and CNT-based ERMs, respectively.…”
Section: Versatility and Working Principle Of Electro-responsive Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Omi et al [55] fabricated CNT-based ERMs via a vacuum-assisted layer-by-layer method. Also, electrophoretic deposition [56] and chemical vapor deposition [17] have been used to obtain hollow fiber type rGO-CNT and CNT-based ERMs, respectively.…”
Section: Versatility and Working Principle Of Electro-responsive Membranesmentioning
confidence: 99%
“…With the assistance of external power, ERMs can conduct additional capabilities that conventional membranes cannot perform. In previous studies, it was demonstrated that electrically responsive membranes (ERMs) can be used to mitigate membrane fouling [17][18][19], monitor membrane fouling propensity [20], self-cleaning [21,22], electrochemically oxidizing organic contaminants [23], controlling permeability and selectivity [24][25][26], energy recovery [27], and controlling membrane wettability [28].…”
Section: Introductionmentioning
confidence: 99%
“…The superhydrophobic surface is one of the hot spots in the research of new materials due to its excellent properties of self‐cleaning, 1 water‐resistant, 2 ice‐resistant, 3 antibacterial, 4 and anticorrosive 5 . By controlling the roughness of the surface and introducing functional groups with low surface energy, great progress has taken place in the research of superhydrophobic material.…”
Section: Introductionmentioning
confidence: 99%
“…The superhydrophobic surface is one of the hot spots in the research of new materials due to its excellent properties of self-cleaning, 1 water-resistant, 2 ice-resistant, 3 antibacterial, 4 and anticorrosive. 5 By controlling the roughness of the surface and introducing functional groups with low surface energy, great progress has taken place in the research of superhydrophobic material. However, due to the inherent fragility of the hierarchy, the wettability of the surface of superhydrophobic materials is compromised under strict and complex physical or chemical conditions, which reduced the service life and application value of the products.…”
Section: Introductionmentioning
confidence: 99%
“…MD is a promising technology for desalting wastewater. It is a thermally driven separation process using a hydrophobic microporous membrane, different from the pressure-driven membrane process [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Heat and mass transfer through the membrane are both involved in the process [ 8 ].…”
Section: Introductionmentioning
confidence: 99%